2016
DOI: 10.1097/igc.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Cytokeratin 19 and Squamous Cell Cancer Antigen in Histologically Negative Sentinel Lymph Nodes of Cervical Squamous Cell Carcinoma

Abstract: Immunohistochemical assessment of both CK19 and SCCAg status in histologically negative sentinel lymph nodes may be a valuable approach for predicting recurrence and survival after curative surgery for cervical squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Michela and Ren each identified elevated pretreatment levels of SCC-Ag as a prognostic factor in early-stage CC. 10,18 Serum AFP, CA153 and CA199 are classical tumor markers with abnormal expression in various human malignancies, 17,19 but we did not find the association of these tumor markers with disease prognosis in early-stage ADC.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Michela and Ren each identified elevated pretreatment levels of SCC-Ag as a prognostic factor in early-stage CC. 10,18 Serum AFP, CA153 and CA199 are classical tumor markers with abnormal expression in various human malignancies, 17,19 but we did not find the association of these tumor markers with disease prognosis in early-stage ADC.…”
Section: Discussioncontrasting
confidence: 58%
“…15,16 Unfortunately, their roles in early ADC disease have not been defined. In addition, other routinely tested tumor markers, such as squamous cell carcinoma antigen (SCC-Ag), alpha-fetoprotein (AFP), carbohydrate antigen 153 (CA153) and carbohydrate antigen 199 (CA199) have been investigated to correlate with prognosis in human malignancies, 10,[17][18][19] but there is no evidence that they are associated with the prognosis of early stage ADC. Moreover, recent studies confirmed that the combination of CEA and CA125 could predict prognosis in gastric cancer, pancreatic cancer and breast cancers, but its utility for early-stage ADC has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we present one of the first reports of the use of OSNA to intra-operatively detect micro-metastasis in early-stage cervical cancer. In our study we demonstrated that all of the first 12 consecutive patients expressed cytokeratin 19 in the primary tumor: this immunohistochemistry test was performed to avoid false negative SLN results, in view of discordant literature reports which described cytokeratin 19 expression in 58.4–100% of the primary tumor sites 23–27…”
Section: Discussionmentioning
confidence: 63%